Filgotinib as induction and maintenance therapy for ulcerative colitis (SELECTION): a phase 2b/3 double-blind, randomised, placebo-controlled trial. Issue 10292 (19th June 2021) - Feagan, Brian G; Danese, Silvio; Loftus, Edward V; Vermeire, Séverine; Schreiber, Stefan; Ritter, Timothy; Fogel, Ronald; Mehta, Rajiv; Nijhawan, Sandeep; Kempiński, Radosław; Filip, Rafał; Hospodarskyy, Ihor; et al.
Summary: Background: The global prevalence of ulcerative colitis is increasing, and induction and maintenance of remission is a crucial therapeutic goal. We assessed the efficacy and safety of filgotinib, a once-daily, oral Janus kinase 1 preferential inhibitor, for treatment of ulcerative colitis. Methods: This phase 2b/3, double-blind, randomised, placebo-controlled trial including two induction studies and one maintenance study was done in 341 study centres in 40 countries. Eligible patients were aged 18–75 years with moderately to severely active ulcerative colitis for at least 6 months before enrolment (induction study A: inadequate clinical response, loss of response to or intolerance to corticosteroids or immunosuppressants, naive to tumour necrosis factor [TNF] antagonists and vedolizumab [biologic-naive]; induction study B: inadequate clinical response, loss of response to or intolerance to any TNF antagonist or vedolizumab, no TNF antagonist or vedolizumab use within 8 weeks before screening [biologic-experienced]). Patients were randomly assigned 2:2:1 to receive oral filgotinib 200 mg, filgotinib 100 mg, or placebo once per day for 11 weeks. Patients who had either clinical remission or a Mayo Clinic Score response at week 10 in either induction study entered the maintenance study. Patients who received induction filgotinib were rerandomised 2:1 to continue their induction filgotinib regimen or to placebo. Patients who received induction placebo continued receiving placebo. The primary endpoint was clinical remission by Mayo endoscopic, rectal bleeding, and stool frequency subscores at weeks 10 and 58. For the induction studies, efficacy was assessed in all randomised patients who received at least one dose of study drug or placebo within that study. For the maintenance study, efficacy was assessed in all patients randomised to any filgotinib treatment group in the induction studies who received at least one dose of study drug or placebo in the maintenance study. Patients who received placebo throughout the induction and maintenance study were not included in the full analysis set for the maintenance study. Safety was assessed in all patients who received at least one dose of the study drug or placebo within each study. This trial is registered with ClinicalTrials.gov, NCT02914522 . Findings: Between Nov 14, 2016, and March 31, 2020, we screened 2040 patients for eligibility. 659 patients enrolled in induction study A were randomly assigned to receive filgotinib 100 mg (n=277), filgotinib 200 mg (n=245), or placebo (n=137). 689 patients enrolled into induction study B were randomly assigned to receive filgotinib 100 mg (n=285), filgotinib 200 mg (n=262), or placebo (n=142). 34 patients in induction study A and 54 patients in induction study B discontinued the study drug before week 10. After efficacy assessment at week 10, 664 patients entered the maintenance study (391 from induction study A, 273 from induction study B). 93 patients continued to receive placebo. 270 patients who had received filgotinib 100 mg in the induction study were randomly assigned to receive filgotinib 100 mg (n=179) or placebo (n=91). 301 patients who had received filgotinib 200 mg in the induction study were randomly assigned to receive filgotinib 200 mg (n=202) or placebo (n=99). 263 patients discontinued treatment in the maintenance study. At week 10, a greater proportion of patients given filgotinib 200 mg had clinical remission than those given placebo (induction study A 26·1% vs 15·3%, difference 10·8%; 95% CI 2·1–19·5, p=0·0157; induction study B 11·5% vs 4·2%, 7·2%; 1·6–12·8, p=0·0103). At week 58, 37·2% of patients given filgotinib 200 mg had clinical remission versus 11·2% in the respective placebo group (difference 26·0%, 95% CI 16·0–35·9; p<0·0001). Clinical remission was not significantly different between filgotinib 100 mg and placebo at week 10, but was significant by week 58 (23·8% vs 13·5%, 10·4%; 0·0–20·7, p=0·0420). The incidence of serious adverse events and adverse events of interest was similar between treatment groups. In the induction studies, serious adverse events occurred in 28 (5·0%) of 562 patients given filgotinib 100 mg, 22 (4·3%) of 507 patients given filgotinib 200 mg, and 13 (4·7%) of 279 patients given placebo. In the maintenance study, serious adverse events were reported in eight (4·5%) of 179 patients given filgotinib 100 mg, seven (7·7%) of 91 patients in the respective placebo group, nine (4·5%) of 202 patients in the filgotinib 200 mg group, and no patients in the respective placebo group. No deaths were reported during either induction study. Two patients died during the maintenance study; neither was related to treatment. Interpretation: Filgotinib 200 mg was well tolerated, and efficacious in inducing and maintaining clinical remission compared with placebo in patients with moderately to severely active ulcerative colitis. Funding: Gilead Sciences.